The Danites,' Puck Magazine, 1908 (Keppler & Schwarzmann, 1908)
Puck' humor magazine featuring a cartoon mock battle scene between cowboys, pioneers, and Native Americans with characters like Hearst, Shearn, Brisbane, Murphy, Ridder, Kern, Watterson, Fingy, Chanler, Parker, Mack, Hisgen, Haskell, and Graves playing the parts. Written beneath the scene is the title "The Danites" with "Another Mountain Meadows Massacre" as the descriptor. On the back is an article highlighting the increasing disparity between living costs and wages focusing on Republican backed tariffs. It then calls for the election of 'Bryan and Kern' for 'lower living expenses'.